2021
DOI: 10.1016/j.heliyon.2021.e06254
|View full text |Cite
|
Sign up to set email alerts
|

Gamification and flipped learning and their influence on aspects related to the teaching-learning process

Abstract: Nowadays, education is going through a moment of methodological transformation. Two of the active methodologies with excellent projection within the educational field are gamification and flipped learning. This study analyzed the methodological contrast between gamification and flipped learning in the subject of Physical Education in three different educational stages to determine the most influential methodology in the training process. Research design was a quasi-experimental research with a sample of 356 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 44 publications
(46 reference statements)
2
46
0
3
Order By: Relevance
“…This undoubtedly causes an increase in the levels of socialization among students [37] and a broad capacity to solve problems in the classroom, both individually and collectively [38]. For this reason, flipped learning gives possibilities of a better acquisition of contents [39], reaching objectives with greater ease [40], which leads to better qualifications of the evaluation processes [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…This undoubtedly causes an increase in the levels of socialization among students [37] and a broad capacity to solve problems in the classroom, both individually and collectively [38]. For this reason, flipped learning gives possibilities of a better acquisition of contents [39], reaching objectives with greater ease [40], which leads to better qualifications of the evaluation processes [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this instrument is positioned as an optimal and improved tool with respect to previous versions of other contexts [26,41,[48][49][50]. With all the above in mind, in this study, the ETLQ was adapted and validated to the Spanish context in order to allow for analysis of the online learning experiences that have emerged as a consequence of the transformation that coronavirus disease 2019 (COVID-19) has caused in learning spaces [59], going from a purely face-to-face and sometimes hybrid scenario to distance learning [60].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies present a combination of FL and gamification [27][28][29], none focusing on developing CTS. Others stress the need to study both techniques compared with a traditional classroom [30]. However, it was found that FL and gamification increase interest in completing pre-class activities and making better quality products [31].…”
Section: Flipped Learning and Gamification For The Development Of Creative Thinking Skillsmentioning
confidence: 99%